Determining Children's Perceptions, Opinions and Attitudes for Sliced Sandwich Breads. Issue 5 (24th September 2014) - Jervis, M.G.; Jervis, S.M.; Guthrie, B.; Drake, M.A.
Abstract The objective of this study was to determine the ideal whole grain bread product for children (8–17 years) using a survey and conjoint analysis. Focus groups (three focus groups, n = 23), emotional response and appearance liking surveys (n = 172), and an adaptive choice‐based conjoint survey (n = 173) were conducted with children. Across elementary, middle and high school‐aged children, children preferred bread with a light crumb (inside of the bread), a light crust and no topping or added textures or visual cues in the crumb. Children had generally negative feelings for breads with dark‐colored crumb and crust, but had generally positive feelings for breads with light‐colored crumb and crust. Breads with white crumb were liked more than bread with dark crumb, regardless of crumb particles, crust or crust topping. Crust color had no impact on overall appearance liking score. These results demonstrate that regardless of age, children like soft breads with light‐colored crumb and crust with no fillings or toppings. Practical Applications Increased consumption of whole grain breads is an effective technique in decreasing obesity in American children. Children's likings of bread products have an inverse relationship with whole grain versus refined grain content. This study demonstrated that development of a whole grain bread product that is desirable to children in both visual appearance and taste is an important step toward increased whole grain consumption by children and that images of attributes and a conjoint analysis in a survey format can be effectively utilized by children to measure their desires.